N-Alkylmorpholines: Potent Dermal and Transdermal Skin Permeation Enhancers - Kristýna Dvořáková; Petr Štěpánek; Jiřina Kroupová; Jarmila Zbytovská (MDPI AG, 2021)
Transdermal drug delivery is an attractive non-invasive method offering numerous advantages over the conventional routes of administration. The main obstacle to drug transport is, however, the powerful skin barrier that needs to be modulated, for example, by transdermal permeation enhancers. Unfortunately, there are still only a few enhancers showing optimum properties including low toxicity and reversibility of enhancing effects. For this reason, we investigated a series of new N-alkylmorpholines with various side chains as potential enhancers in an in vitro permeation study, using three model permeants (theophylline, indomethacin, diclofenac). Moreover, electrical impedance, transepidermal water loss, cellular toxicity and infrared spectroscopy measurements were applied to assess the effect of enhancers on skin integrity, reversibility, toxicity and enhancers' mode of action, respectively. Our results showed a bell-shaped relationship between the enhancing activity and the hydrocarbon chain length of the N-alkylmorpholines, with the most efficient derivatives having 10-14 carbons for both transdermal and dermal delivery. These structures were even more potent than the unsaturated oleyl derivative. The best results were obtained for indomethacin, where particularly the C10-14 derivatives showed significantly stronger effects than the traditional enhancer Azone. Further experiments revealed reversibility in the enhancing effect, acceptable toxicity and a mode of action based predominantly on interactions with stratum corneum lipids.